2014
DOI: 10.1089/jop.2013.0194
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Lysophospholipids: Role in Regulation of Aqueous Humor Outflow and Intraocular Pressure in the Context of Pathobiology and Therapy of Glaucoma

Abstract: Homeostasis of aqueous humor (AH) outflow and intraocular pressure (IOP) is essential for normal vision. Impaired AH outflow through the trabecular meshwork (TM) and a resultant elevation in IOP are common changes in primary open-angle glaucoma (POAG), which is the most prevalent form of glaucoma. Although elevated IOP has been recognized as a definitive risk factor for POAG and lowering elevated IOP remains a mainstay for glaucoma treatment, little is known about the molecular mechanisms, especially external … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 114 publications
0
30
0
Order By: Relevance
“…[17][18][19][20][21][22][23][24] LPA also influences the contractile and adhesive properties of TM and SC cells, and is suggested to be involved in the pathogenesis of glaucoma. [25][26][27][28][29][30] LPA is derived, under various conditions both in cells and biological fluids, mainly from lysophosphatidylcholine (LPC) and predominantly through the lysophospholipase D (lysoPLD) activity of ATX. [31][32][33][34][35] ATX is a secreted glycoprotein, widely present in biological fluids, and originally isolated from the supernatants of melanoma cells as an autocrine motility stimulation factor.…”
mentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24] LPA also influences the contractile and adhesive properties of TM and SC cells, and is suggested to be involved in the pathogenesis of glaucoma. [25][26][27][28][29][30] LPA is derived, under various conditions both in cells and biological fluids, mainly from lysophosphatidylcholine (LPC) and predominantly through the lysophospholipase D (lysoPLD) activity of ATX. [31][32][33][34][35] ATX is a secreted glycoprotein, widely present in biological fluids, and originally isolated from the supernatants of melanoma cells as an autocrine motility stimulation factor.…”
mentioning
confidence: 99%
“…Recent studies have shown the effect on AH outflow by selected species of others classes of lipids including sphingolipids and ceramides [6, 38, 39]. However, the identification of all lipid species of these classes in the AH remained unknown, which is why we undertook the current mass spectrometric investigation.…”
Section: Discussionmentioning
confidence: 99%
“…1, Table 4 and Supplementary Table S3) involved in sphingolipid metabolism [45]. The application of specific sphingolipids such as S1P has been known to modulate AH outflow [6, 46]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations